WEB 2.0 TOOLS IN EDUCATION - MAREŠOVÁ, Hana (Trends in education, 2008)
The article describes the possibilities of using Web 2.0 tools in education. The analyzed tools are presented by some examples from internet network and from the seminars Internet and Multimedia in the Czech Language Education, New Media and Cyberculture and Presentation and Discussion Techniques, which have been realized at the Department of Czech Language and Literature (Faculty of Education, Palacký University in Olomouc).
Keywords: information and communication technologies; Web 2.0; virtual education; Multi User Virtual Environment